(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2021)
The research included several axes through the use of a program that includes clinical exercises and drugs to reduce bone density loss in women with osteoporosis, the study aims to identify the proposed program to reduce osteoporosis among women. The study was conducted on three groups of women with osteoporosis (program - exercise - medication) and their ages ranged from 40-50 years and their number was (27) affected, they were divided into three groups, for each group (9) women with osteoporosis, the first group included the program (clinical exercises - medication) and the second group included exercises, while the third group included medicines, the experimental approach was used to design the three equivalent groups, where the program was applied, which includes (24) weeks with a rate of (48) treatment units and the time of the treatment unit (20) minutes, health fitness for the injured, the results of the study indicated an improvement in the loss of bone mass for all groups and a greater improvement in favor of the program group (clinical exercises - medication). The study recommended the use of the proposed program for women with osteoporosis.